Perlindungan Hukum bagi Penghayat Kepercayaan untuk Mengatasi Diskriminasi dan Marginalisasi - Sindi Marita Ningsih; Anang Dony Irawan (JATISWARA, 2026)
Adherents of indigenous belief systems in Indonesia continue to face various forms of discrimination and marginalization in social and administrative spheres. Although the 1945 Constitution of the Republic of Indonesia explicitly guarantees freedom of religion and belief, the implementation of these constitutional guarantees has not fully provided equal legal protection for adherents of belief systems outside the officially recognized religions. The main issues encountered include limited legal recognition of identity, obstacles in accessing public services, and persistent social stigma within society. This study aims to analyze the forms of legal protection available to adherents of indigenous belief systems and to assess their effectiveness in eliminating discriminatory practices. The research employs a normative juridical method with a statutory approach and case studies. Constitutional Court Decision Number 97/PUU-XIV/2016 represents an important milestone in the recognition of the rights of adherents of belief systems, particularly regarding the inclusion of belief identity in population administration documents. This decision has strengthened the legal standing of adherents of indigenous beliefs and encouraged regulatory reforms in the field of population administration. Nevertheless, the implementation of this decision continues to face challenges at the regional level, as well as social resistance. Therefore, stronger policy measures and effective oversight are required to ensure the fair and equal fulfillment of the constitutional rights of adherents of indigenous belief systems.